Regular long runs and higher training volumes are associated with better running economy durability in performance matched well-trained male runners - Zanini, M.; Folland, J. P.; Blagrove, R. C. (Medicine & Science in Sports & Exercise, 2026)
Introduction Running economy (RE) deteriorates during prolonged running (i.e., RE durability), although it is unknown if runners` training characteristics influence RE durability. Furthermore, the extent of the decrement in neuromuscular capabilities after running could also contribute to differences in RE durability. Therefore, this study aimed to compare RE durability during a 90-min run and the decrements in neuromuscular capabilities, between athletes who did or did not practice regular long runs, while pair-matched for performance status.